2021
DOI: 10.1186/s12884-021-03755-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of prevalence of insomnia in the third trimester of pregnancy

Abstract: Background Sleep disorders, which are among the foremost important medical care issues, are prevalent in pregnancy. The present study is a meta-analysis of the prevalence of insomnia in the third trimester of pregnancy. This study aims to systematically review the overall prevalence of insomnia in the third trimester of pregnancy through conducting a meta-analysis. Method The literature used in this meta-analysis for the topic discussed above were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The present study demonstrated that sleep quality deteriorates with increasing gestational age. This is consistent with the results reported by Shojaie et al (32), Facco et al (33), and a recent systematic review by Salari et al (34), which demonstrated that women had sleep disorders and suffered from poor sleep quality in the final months of their pregnancy. This study showed that sleep quality and gestational age are significantly correlated.…”
Section: Discussionsupporting
confidence: 93%
“…The present study demonstrated that sleep quality deteriorates with increasing gestational age. This is consistent with the results reported by Shojaie et al (32), Facco et al (33), and a recent systematic review by Salari et al (34), which demonstrated that women had sleep disorders and suffered from poor sleep quality in the final months of their pregnancy. This study showed that sleep quality and gestational age are significantly correlated.…”
Section: Discussionsupporting
confidence: 93%
“…It is curious that in our sample, only 44 pregnant women out of the final 292 included (15.07%) had insomnia. The literature generally reports higher prevalence rates in the third trimester of pregnancy, the time of our assessment, from 39.7% [ 9 ] to 42.4% [ 63 ]. It is possible that the different diagnostic methods used account for the discrepancy in findings.…”
Section: Discussionmentioning
confidence: 99%
“…From the second trimester to the third trimester, the average PSQI score increased by 1.68 points, which showed that poor sleep quality was common during pregnancy 3 . Recently, a systematic review confirmed that the prevalence of insomnia in the third trimester of pregnancy is 42.4%, which meant approximately one‐third of pregnant women failed to maintain enough sleep 64 . Furthermore, sleep satisfaction and duration decline sharply after delivery, and are difficult to fully recover to pre‐pregnancy 65 .…”
Section: Discussionmentioning
confidence: 99%